FORMATION OF MOTIVATION FOR PHYSICAL CULTURE AND SPORTS IN MILITARY PERSONNEL WITH HEALTH LIMITATIONS - Obraztsov M.S. ,; Islamov V.A. ,; Savchenko O.A. ,; Elizarov D.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify factors that influence the motivation of military personnel with health limitations to engage in physical activity and participate in sports events. Methods and structure of the study. Scientific work was carried out at the Kirov Military Medical Academy, St. Petersburg. The experiment involved 76 servicemen with health limitations who are undergoing rehabilitation and professional retraining. In the course of the study, the following were carried out: questionnaires, interviews, conversations, pedagogical observation, methods of mathematical statistics were applied to the results obtained. Results and conclusions. The main motivational factors are revealed, their relationship with knowledge about physical culture and sports is revealed. The results obtained made it possible to form practical recommendations for the activities of specialists involved in the rehabilitation and social adaptation of military personnel with health limitations.